2023
DOI: 10.1128/spectrum.01453-23
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and metabolomics reveal the compatible relationship among Suillus bovinus , Phialocephala fortinii , and their co-host, Pinus massoniana

Xueguang Sun,
Yanzhen Zhao,
Guijie Ding

Abstract: Ectomycorrhizal (ECM) fungi and dark septate endophytes (DSEs) can both form a symbiotic relationship with the same host plant. However, the interactions that occur among these two types of fungi and their co-hosts are largely unknown. Here, we investigated interactions that occur among the ECM fungus Suillus bovinus , the DSE Phialocephala fortinii , and their co-host Pinus massoniana . We used both scanning electron microscopy and optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Such priority effects (Fukami, 2015) may be stronger in ectomycorrhizal fungal communities (Kennedy, 2010) than in arbuscular mycorrhizal fungal communities (Werner and Kiers, 2015) potentially because ectomycorrhizal fungi can defend their territories by forming dense hyphal structures (mantles) surrounding host roots (Smith and Read, 2008). Potentially due to the defensive abilities of ectomycorrhizal fungi, the inferred negative interations between ectomycorrhizal fungi and fungi in other ecological guilds (Table 3) may be asymmetric (Sun et al, 2023). Indeed, an experimental study has shown that ectomycorrhizal fungi can impose asymmetric suppressive impacts on root-endophytic fungi (Reininger & Sieber, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such priority effects (Fukami, 2015) may be stronger in ectomycorrhizal fungal communities (Kennedy, 2010) than in arbuscular mycorrhizal fungal communities (Werner and Kiers, 2015) potentially because ectomycorrhizal fungi can defend their territories by forming dense hyphal structures (mantles) surrounding host roots (Smith and Read, 2008). Potentially due to the defensive abilities of ectomycorrhizal fungi, the inferred negative interations between ectomycorrhizal fungi and fungi in other ecological guilds (Table 3) may be asymmetric (Sun et al, 2023). Indeed, an experimental study has shown that ectomycorrhizal fungi can impose asymmetric suppressive impacts on root-endophytic fungi (Reininger & Sieber, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Suillus bovinus , an edible mushroom belonging to the Suillus genus, is broadly distributed across various regions globally ( Feng et al, 2022 ). In recent years, research about S. bovinus focus mainly on the mechanisms related to symbiotic interactions with trees ( Sun et al, 2023 ). Additionally, the pharmacological studies indicated that S. bovinus possessed the effect of inhibiting CYP enzymes ( Huang et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also contains anticancer substances, with antitumor, antioxidant, and anti-inflammatory effects, thus providing both medicinal and edible benefits [ 4 , 5 ]. However, with unique growth and development characteristics, the domestication and artificial cultivation of this fungus remain challenging [ 6 , 7 ]. Thus, there is growing interest in understanding the mycorrhizal formation process of S. bovinus , as well as the underlying molecular mechanisms to facilitate strategies for the effective cultivation of this ECM fungus.…”
Section: Introductionmentioning
confidence: 99%